MENGATASI CYBERBULLYING DAN HOAX DENGAN LITERASI DIGITAL BAGI SISWA SEKOLAH MENENGAH - Husda, Nur Elfi; Rorong, Michael Jibrael; Rasid Ridho, Muhammad; Nurhabsyina, Nurhabsyina; Fabiola, Fanie; Khairudin, Khairudin (LPPM Universitas Bina Bangsa, 2025)
The rapid development of information technology today must be anticipated by paying attention to both the positive and negative impacts it brings. One essential skill for society, especially school students or teenagers, is digital literacy in their daily lives, whether at school or in the community. This is increasingly important as cases of cyberbullying among teenagers are rising, as well as the spread of hoaxes, which, if not properly understood, can have harmful effects on students. Therefore, the purpose of this community service initiative is to improve digital literacy among high school students to enhance the positive impacts and reduce the negative impacts of information technology advancements. This activity is conducted in the form of a seminar. The seminar results show that students gain an understanding of the dangers of cyberbullying and develop a good grasp of digital literacy.